Group-scheduling mechanism for large-scale time-sensitive network - Xuesong QIU; Xuchuan HUANG; Wencui LI; Wenjing LI; Shaoyong GUO (Tongxin xuebao)
In order to achieve the deterministic delay of time-triggered traffic in a large-scale time-sensitive network,a kind of group-scheduling mechanism was proposed.By designing a topology pruning strategy and a flow grouping strategy based on spectral clustering,the impact of the rapid increase in network topology scale and traffic scale on the speed of scheduling response was avoided,and the scheduling calculation efficiency was improved.The results of experiment show that the mechanism can solve the model in a relatively short time for large-scale scheduling problem and achieve a relatively high scheduling success rate.